Install Steam
login
|
language
简体中文 (Simplified Chinese)
繁體中文 (Traditional Chinese)
日本語 (Japanese)
한국어 (Korean)
ไทย (Thai)
Български (Bulgarian)
Čeština (Czech)
Dansk (Danish)
Deutsch (German)
Español - España (Spanish - Spain)
Español - Latinoamérica (Spanish - Latin America)
Ελληνικά (Greek)
Français (French)
Italiano (Italian)
Bahasa Indonesia (Indonesian)
Magyar (Hungarian)
Nederlands (Dutch)
Norsk (Norwegian)
Polski (Polish)
Português (Portuguese - Portugal)
Português - Brasil (Portuguese - Brazil)
Română (Romanian)
Русский (Russian)
Suomi (Finnish)
Svenska (Swedish)
Türkçe (Turkish)
Tiếng Việt (Vietnamese)
Українська (Ukrainian)
Report a translation problem
= ((e^(ix))^n-(e^(-ix))^n)/(2i)
= ((cosx+isinx)^n-(cosx-isinx)^n)/(2i)
= sum_(k=0)^(n)(n; k)(cos^kx(isinx)^(n-k)-cos^kx(-isinx)^(n-k))/(2i)
= sum_(k=0)^(n)(n; k)cos^kxsin^(n-k)x(i^(n-k)-(-i)^(n-k))/(2i)
= sum_(k=0)^(n)(n; k)cos^kxsin^(n-k)xsin[1/2(n-k)pi].